Role of Body Mass Index, Waist-to-Height and Waist-to-Hip Ratio in Prediction of Nonalcoholic Fatty Liver Disease - Rui-Dan Zheng; Zhuo-Ran Chen; Jian-Neng Chen; Yan-Hui Lu; Jie Chen (Gastroenterology Research and Practice)
Objective. To investigate the anthropometric indicators that can effectively predict the nonalcoholic fatty liver disease (NAFLD). Methods. The height, body weight, waist and hip circumference were measured, and body mass index (BMI), waist-to-height (WHtR) and waist-to-hip ratio (WHR) were calculated. M-H chi square test, logistic regression analysis, and receiver-operating characteristic (ROC) curve were employed for the analysis of risk factors. Patients or Materials. 490 patients were recruited, of whom 250 were diagnosed as NAFLD and 240 as non-NAFLD (control group). Results. Compared with the control group, the BMI, WHR, and WHtR were significantly higher in patients with NAFLD. Logistic regression analysis showed that BMI and WHR were effective prognostic factors of NAFLD. In addition, WHR plays a more important role in prediction of NAFLD by the area under curve. Conclusion. WHR is closely related to the occurrence of NAFLD. We assume that WHR is beneficial for the diagnosis NAFLD.